School Heads’ Managerial Skills and School Climate in TESDA-Technical and Vocational Institutions of Negros Oriental - Caluscusin, Michael Mark; Bajas-Caluscusin, Anna Maneleine (Journal of Interdisciplinary Perspectives, 2025)
This study addresses the gap in understanding how school heads’ managerial skills influence the school climate in technical and vocational education settings. Specifically, it explores the relationship between the managerial competencies of school heads and the school climate as perceived by trainers and school administrators in TESDA Region VII - Negros Oriental Technical and Vocational Institutions (TVIs). The study aimed to determine the extent of school heads’ managerial skills and their correlation with school climate, thereby providing evidence-based insights for leadership improvement. Employing a quantitative-correlational research design, the study surveyed 138 trainers and 14 school heads using a researcher-adapted instrument from the Teaching and Learning International Survey (TALIS) initiated by the Organization for Economic Co-operation and Development (OECD). Results showed that school heads exhibited strong managerial skills, particularly in conceptual, technical, and human domains, with teamwork being the most highly rated. Conversely, emotional sensitivity and communication skills ranked lowest, suggesting a need for targeted development in these areas. The findings also revealed that school climate is significantly associated with several managerial skill domains, including problem-solving, results orientation, communication, development of others, and organizational ability. Data showed that a favorable school climate could foster student innovation, self-awareness, and personal growth, which are key outcomes aligned with the goals of technical and vocational education. The study highlights the importance of developing leadership competencies to create a more effective and supportive educational environment. It recommends implementing a leadership development program to strengthen underdeveloped skill areas and address issues related to instructional quality and student discipline. Further studies are encouraged to examine the generalizability of these results across other regions and educational settings.